Isolation, Characterization and Biological Activities of Phytoconstituents from Lonchocarpus Eriocalyx Harms Leaves - Manguro, Lawrence Onyango Arot; Owuor, Phillip Okind; Ochung, Angeline Atieno (Trends in Phytochemical Research (TPR), 2018)
The plant species Lonchocarpus eriocalyx Harms (Fabaceae) is a deciduous slender tree or shrub which grows up to 15 m tall. It is an important medicinal plant in Kenya used to treat a wide range of ailments including eye infection, wound and ulcer. However, little is known about its chemical constituents. The present study aims to isolate secondary metabolites from the plant leaves along with their various biological activities. Eight compounds, namely friedelin (1), lupenone (2), lupeol (3), stigmasterol (4), chrysin (5), stigmasterol 3-O-ß-glucoside (6), apigenin (7) and 3,5,7,2’,4’-pentahydroxyflavonol (8) were isolated from the CH2Cl2 and MeOH extracts of Lonchocarpus eriocalyx Harms leaves. Their structures were determined by using physical and spectroscopic methods as well as comparison with literature data. The CH2Cl2 and MeOH extracts together with the isolated compounds were subjected to an array of biological tests including antiplasmodial,larvicidal and mosquitocidal, antimicrobial and anti-inflammatory assays.The compounds 1-4 and 6 together with their anti-inflammatory activities are reported from this plant for the first time.
Keywords: Lonchocarpus eriocalyx Harms; Fabaceae; Phytoconstituents; Biological activities